Perbandingan Struktur Lembaga Pendidikan Islam dan Kurikulum di Indonesia, Iran dan Arab Saudi - Muvid, Muhamad Basyrul (Tawazun: Jurnal Pendidikan Islam, 2020)
Comparative study of education between countries is carried out to find out the weaknesses and strengths between the education systems conducted in each of these countries. So that it can be used as input and solutions for countries whose educational systems are still weak. This paper seeks to examine and find and analyze comparisons of Islamic education in Indonesia, Iran and Saudi Arabia regarding the structure of Islamic educational institutions and curricula in the three countries. The results of this study include: First, the structure of Islamic educational institutions in Indonesia includes PAUD, RA, MI, MTs, MA and Universities, while in Iran Pend. Pre-School-Pend. Basic-Pend. Middle-Pend. High. In Saudi Arabia Pre-School-Education. Basic-Pend. Intermediate-Pend. Secondary-Pend. High. Second, the curriculum in Islamic education institutions in Indonesia consists of religious knowledge and supplemented with general subjects. In Iran the integration of the General Religion-Science curriculum, but the allocation of general knowledge is more and varied than in Indonesia. In Saudi Arabia, too, is the integration between religious and general science, studies of religion and general science in Saudi Arabia are adapted to the educational model there. Abstrak Studi perbandingan pendidikan antar negara dilakukan untuk mengetahui kelemahan dan kelebihan antar sistem pendidikan yang diselenggarakan pada masing-masing negara tersebut. Sehingga bisa dijadikan masukan dan solusi bagi negara yang sistem pendidikannya masih lemah. Tulisan ini berusaha mengkaji dan menemukan serta menganalisis perbandingan pendidikan Islam di Indonesia, Iran dan Arab Saudi mengenai struktur lembaga pendidikan Islam dan kurikulum di tiga negara tersebut. Hasil kajian ini meliputi: Pertama, struktur lembaga pendidikan Islam di Indonesia meliputi PAUD, RA, MI, MTs, MA dan Perguruan Tinggi, sedangkan di Iran Pend. Pra Sekolah-Pend.Dasar-Pend.Menengah-Pend. Tinggi. Di Arab Saudi Pra-Sekolah-Pend. Dasar-Pend. Menengah-Pend. Sekunder-Pend. Tinggi. Kedua, kurikulum di lembaga pendidikan Islam yang ada di Indonesia terdiri atas ilmu agama dan ditambah dengan mata pelajaran umum. Di Iran integrasi kurikulum Agama-Ilmu Umum, namun alokasi ilmu umum lebih banyak dan bervariasi dibanding di Indonesia. Di Arab Saudi juga demikian integrasi antara ilmu agama dan umum, kajian-kajian ilmu agama dan umum di Saudi disesuaikan dengan model pendidikan di sana.